Impact of a brief training on motivational interviewing and the 5A's approach on weight‐related counseling practices of pediatricians - Jean A. Welsh; Samantha J. Lange; Janet Figueroa; Stephanie Walsh; Holly Gooding; Patricia Cheung (Wiley, 2022)
Abstract Background Pediatric primary healthcare providers are well‐positioned to provide healthy lifestyle and weight management related counseling but many lack training in evidence‐based messages and methods. Objectives We assessed the impact of a brief, easy‐to‐access training for pediatric healthcare providers, (the Strong4Life Provider Training), designed to introduce/review current evidence‐based messages and methods and improve healthy weight‐related assessment and counseling practices. Methods Following their well‐child visit, a convenience sample of children 12-17 years and parents of children 6-11 years (N = 121) of randomly selected Strong4Life trained (N = 15) and untrained (N = 15) pediatricians were administered a survey designed to assess the frequency, content, and patient satisfaction with weight management‐related counseling provided. Results from parents and patients of trained pediatricians (N = 62) compared to those from parents and patients of untrained pediatricians (n = 59) were compared using chi‐square tests. Generalized estimating equations were used to account for lack of independence among respondents from the same practice. P‐values less than 0.05 were considered to be statistically significant. Results Parents/patients of trained pediatricians were more likely than those of an untrained pediatrician to report having been asked about child's consumption of fruit/vegetables, 57 (92%) versus 44 (75%), p = 0.04 and sugary drinks, 50 (81%) versus 29 (49%), p = 0.005, and their readiness for behavior change, 47 (76%) versus 29 (49%), p = 0.005, and to set a behavior change goal, 36 (59%) versus. 23 (40%), p = 0.005. Regardless of training status, physical activity, screen time, and weight status were assessed for most patients, and most were satisfied with the discussion. Few (21%) were asked about barriers to behavior change.